واقع ممارسة معلمات الریاضیات لمهارات التفکیر الناقد من وجهة نظر طالبات المرحلة الثانویة بمدینة الریاض - الشهري، هیاء بنت محمد; القحطانی، رمش بنت ناصر (الجمعية المصرية لتربويات الرياضيات, 2019)
هدفت هذه الدراسة إلى التعرف على واقع ممارسة معلمات الرياضيات لمهارات التفكير الناقد من وجهة نظر طالبات المرحلة الثانوية بمدينة الرياض. واتبعت الدراسة المنهج الوصفي، وتم بناء استبانة والتأكد من صدقها وثباتها، وصلاحيتها للتطبيق، وذلك قبل توزيعها على العينة بالطريقة العشوائية البسيطة والتي بلغت (424) طالبة من طالبات المرحلة الثانوية بمدينة الرياض. وتوصلت الدراسة إلى أن مفردات عينة الدراسة موافقات دائماً على ممارسة معلمات الرياضيات لمهارات التفكير الناقد، ومن أبرز مهارات التفكير الناقد التي تمارسها معلمات الرياضيات هي مهارة التفسير، تليها مهارة الاستنباط، ثم مهارة الاستنتاج، وأخيراً مهارة تقويم الحجج. ولم تظهر النتائج وجود فروق ذات دلالة إحصائية عند مستوى (0.05) فأقل في اتجاهات مفردات عينة الدراسة حول (مهارة التفسير، مهارة تقويم الحجج، مهارة الاستنباط، مهارة الاستنتاج، واقع ممارسة معلمات الرياضيات لمهارات التفكير الناقد) باختلاف متغير نوع المدرسة. بينما توجد فروق ذات دلالة إحصائية عند مستوى (0.01) فأقل في اتجاهات مفردات عينة الدراسة حول (مهارة التفسير، مهارة تقويم الحجج، مهارة الاستنباط، مهارة الاستنتاج، واقع ممارسة معلمات الرياضيات لمهارات التفكير الناقد) باختلاف متغير الصف الدراسي لصالح الصف الثالث الثانوي. وفي ضوء النتائج أوصت الباحثتان بعدة توصيات، منها: حث معلمات الرياضيات على ممارسة مهارات التفكير الناقد داخل الفصل، وتوعية المعلمات في كافة التخصصات بأهمية التفكير الناقد للطالبات وذلك لجميع المراحل والصفوف.
This study aimed to identify the reality about practicing of mathematics female teachers critical thinking skills from the point of view of female secondary school students in Riyadh. The study using the descriptive methodology, and create a questionnaire, which was arbitrated and calculated validity before distributed to randomly selected members (424) female students in secondary school in Riyadh. The results of the study: study sample always approves the practice of mathematics female teachers for critical thinking skills, and among the most prominent critical thinking skills is (interpretation, inference, deduction, evaluating arguments). It did not difference at the level (0.05) in the study sample about (interpretation, inference, deduction, evaluating arguments, and the reality about practicing of mathematics female teachers critical thinking skills) according of the school type. But it was differences at the level (0.01) in the study sample about (interpretation, inference, deduction, evaluating arguments, and the reality about practicing of mathematics female teachers critical thinking skills) according of the level to the third level. The study recommended the following: Urging mathematics female teachers to practice critical thinking skills in the classroom, and educating all teachers about the importance of critical thinking for students.
Keywords: التفكير الناقد -- مهارات التفکیر الناقد -- تدريس الرياضيات -- معلم الریاضیات -- طلبة المرحلة الثانویة -- الریاض